Effects of the Implementation of Inquiry-Based Learning in Relation to Students’ Autonomy (2024)
ABSTRACT: The following Case Study delves into the effects on autonomy when using Inquiry-based Learning with 10th and 11th grade students, at a public school located in Itagüí. As a part of a new initiative called Investigación Escolar, the school tasked students with developing their own research projects, partaking in a Problem-based Learning approach complemented by a Collaborative Learning approach, openly choosing issues related to their environment and working in small groups. Given this is a cross-curricular approach, students had to add to their research projects from all school subjects, guided by their teacher’s instructions. We performed class observations, interviewed teachers that were directly involved with the implementation of this pedagogical innovation, analyzed students’ logbooks and their responses to questionnaires, looking to study students’process during the development of their research projects, as well as teachers’ and students’ perceptions in terms of students’ autonomy. Doing so, we were able to verify that, during the school year, working on their projects, students became less dependent on their teachers, and their interest in their learning process increased.